The power of professional ideals: Understanding and handling victims’ emotions in criminal cases - Johansen, Louise Victoria (International review of victimology, 2023)
This article explores how criminal justice actors interpret and process victims’ emotional expressions. On the basis of a qualitative study on the interactions between legal institutions and victims of violence in Denmark, the article demonstrates how police officers, prosecutors, victims’ counsel and judges each separately understand and evaluate victims’ emotional reactions. These actors interpret victims’ feelings according to their own professional roles and motivations so as to gain an overview of a case and the actions required of them in relation to it, resulting in quite different perceptions of victims’ needs and degree of trustworthiness. At the same time, professionals also interact across institutions by writing and exchanging case files, and in so doing police officers’ perceptions of victim reactions are often disclosed to both prosecutors and judges. This article contributes to existing knowledge of how different professional ideals specifically influence the handling of victims and their emotional needs, while the more general consensus on ‘appropriate emotions’ simultaneously generates knowledge across professions and institutional settings.